RESEARCH OF THE SECONDARY MARKET OF REAL ESTATE OF KHARKIV: Array - , С. М., Р. С., В. В., Л. М. (Municipal economy of cities. Series: «Economy science», 2018)
The purpose of the article is to develop a methodology for calculating the average real estate value based on a deep study of the secondary real estate market of Kharkiv. To solve the purpose of the article, the following tasks are assigned: - analyze the price proposals on the secondary real estate market;- to explore ways of developing such segments of the secondary real estate market as one, two and three-bedroom apartments;- to analyze the range of prices in the secondary market of Kharkiv and to investigate the tendencies of changing the value of real estate objects in the secondary market;- to substantiate the prices corrected on the results of researches in the secondary real estate market and on the basis of the conducted research show the prospects for the development of the secondary real estate market.Investigated proposals within the city, analysis of separate segments of the secondary real estate market. The market analysis has shown that many secondary market analytical studies have significant discrepancies and a rather large price range. By the end of the year, there will be stabilization and insignificant growth in the market There are factors that stimulate the further more active development of the secondary real estate market: growing demand in the real estate market; stabilization processes in the economy; relative stabilization of the hryvnia exchange rate; decrease of inflation rates; stabilization of the investment climate; accumulation of free money in the population. Keywords: market research, secondary market, purchase and sale.